Fast-ion transport in low density L-mode plasmas at TCV using FIDA spectroscopy and the TRANSP code. (19th September 2017) - Geiger, B; Karpushov, A N; Duval, B P; Marini, C; Sauter, O; Andrebe, Y; Testa, D; Marascheck, M; Salewski, M; Schneider, P A
Abstract: Experiments with the new neutral beam injection source of TCV have been performed with high fast-ion fractions (>20%) that exhibit a clear reduction of the loop voltage and a clear increase of the plasma pressure in on- and off-axis heating configurations. However, good quantitative agreement between the experimental data and TRANSP predictions is only found when including strong additional fast-ion losses. These losses could in part be caused by turbulence or MHD activity as, e.g. high frequency modes near the frequency of toroidicity induced Alfvén eignmodes are observed. In addition, a newly installed fast-ion D-alpha (FIDA) spectroscopy system measures strong passive radiation and, hence, indicates the presence of high background neutral densities such that charge-exchange losses are substantial. Also the active radiation measured with the FIDA diagnostic, as well as data from a neutral particle analyzer, suggest strong fast-ion losses and large neutral densities. The large neutral densities can be justified since high electron temperatures (3–4 keV), combined with low electron densities (about 2 × 10 19 m −3 ) yield long mean free paths of the neutrals which are penetrating from the walls.